The Macro-economic Impact of Cross-border eCommerce in the EU - Joseph Francois; Bertin Martens; Fan Yang (European Commission, Joint Research Centre (JRC), 2014)
We use data on cross-border e-commerce between EU Member States to estimate the implied cross-border trade cost reduction when consumers move from offline to online consumption. We plug this trade cost estimate into a macro-sector multi-country CGE model to estimate the impact of online retailing on consumers as well as producers. We find that cross-border e-commerce increases real household consumption. However, the domestic spill-over effect squeezes price margins in the retail sector and has a negative output effect for that sector. The resulting retail sector efficiency gains have a positive effect on production in other sectors. The combined macro-economic effect of these transmission channels is generally positive for EU Member States, ranging between 0.07 and 0.25 per cent of GDP. As such, this paper adds an innovative macro-perspective to existing micro-economic estimates of the impact of e-commerce on consumer welfare.
Keywords: F14; C54; 330; e-commerce; online trade; cross-border trade; international trade; EU digital single market; CGE model; non-tariff barriers